2011
DOI: 10.1103/physreve.83.056120
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of three-dimensional, nonbonded random fiber networks

Abstract: The mechanical behavior of an ensemble of athermal fibers forming a nonbonded network subjected to triaxial compression is studied using a numerical model. The response exhibits a power law dependence of stress on the dilatation strain and hysteresis upon loading and unloading. A stable hysteresis loop results after the first loading and unloading cycle. In the early stages of compaction, strain energy is associated primarily with the bending of fibers, while at higher densities, it is stored primarily in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 33 publications
2
28
1
Order By: Relevance
“…A broad range of models exists for the modulus of an assemblage of non-crosslinked, non-woven fibers [58, 59, 60, 61, 62]. We applied such models to predict the direction-dependent response of a scaffold clamped and stretched at an angle θ 0 to the dominant direction.…”
Section: 1 Multiscale Model Of the Effect Of Mineralization Time Omentioning
confidence: 99%
“…A broad range of models exists for the modulus of an assemblage of non-crosslinked, non-woven fibers [58, 59, 60, 61, 62]. We applied such models to predict the direction-dependent response of a scaffold clamped and stretched at an angle θ 0 to the dominant direction.…”
Section: 1 Multiscale Model Of the Effect Of Mineralization Time Omentioning
confidence: 99%
“…Rodney et al also simulated a packing made of a self‐entangled single long coiled wire subject to both tension and compression and found that the packing shows unusual, reversible dilatancy behavior with the Poisson' ratio below 0 in tension and above 0.5 in compression. The fiber stiffness was found to have a significant influence on the compression behavior in the previous simulations . The exponent of the power law, n , depended on the ratio of the bending to axial stiffness of the fibers .…”
Section: Introductionmentioning
confidence: 78%
“…The fiber stiffness was found to have a significant influence on the compression behavior in the previous simulations . The exponent of the power law, n , depended on the ratio of the bending to axial stiffness of the fibers . When the base fiber network has a very small ratio of the bending to axial stiffness of the fibers, the addition of a small fraction of stiffer fibers dramatically increased the stiffness of the composite by orders of magnitude .…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In most studies to date all fibers in the network are considered of the same type [5,6,7,8,9] (networks made from dissimilar fibers are studied in [10]) and are, in general, of circular crosssection. However, many athermal fibers have non-circular sections which are characterized by two principal moments of inertia, !…”
Section: Introductionmentioning
confidence: 99%